Internship Experience and Organizational Attractiveness: A Realistic Job Fit Perspective. (April 2023) - Sekiguchi, Tomoki; Mitate, Yoshitaka; Yang, Yunyue
Although job seekers often rely on indirect or inaccurate information to assess the attractiveness of potential employers, internship experience provides more realistic and accurate information, which may influence organizational attractiveness. Through the ex-ante and ex-post (i.e., pre-internship and post-internship) research design with a sample of Japanese undergraduate students in a university-sponsored internship program, we found that, although organizational attractiveness on average declined after the internship, skill variety and feedback from employees in the internship job were positively related to perceived needs-supplies (NS) fit beyond the effect of its pre-internship level. The NS fit, in turn, was related to organizational attractiveness beyond the effect of its pre-internship level. Moreover, some of the above mediating effects were stronger for interns with high social skill and/or high self-esteem. Our findings highlight the importance of the effect of internships on college students' school-to-work transition.